2015
DOI: 10.1038/srep10124
|View full text |Cite
|
Sign up to set email alerts
|

The aftereffect of perceived duration is contingent on auditory frequency but not visual orientation

Abstract: Recent sensory history plays a critical role in duration perception. It has been established that after adapting to a particular duration, the test durations within a certain range appear to be distorted. To explore whether the aftereffect of perceived duration can be constrained by sensory modality and stimulus feature within a modality, the current study applied the technique of simultaneous sensory adaptation, by which observers were able to simultaneously adapt to two durations defined by two different sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 55 publications
(63 reference statements)
5
22
2
Order By: Relevance
“…In line with previous studies (Heron et al, 2012;Li et al, 2015b;Shima et al, 2016), Experiment 1 showed a strong modulation of duration adaptation. Considering that the duration aftereffect is not observed when the duration of the adapting stimulus matched the duration of the test stimulus, the absence of any significant difference between the "adapt equal" and the "adapt longer" conditions in the present study suggests that there was no duration aftereffect after repetitive exposure to a relatively long stimulus.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with previous studies (Heron et al, 2012;Li et al, 2015b;Shima et al, 2016), Experiment 1 showed a strong modulation of duration adaptation. Considering that the duration aftereffect is not observed when the duration of the adapting stimulus matched the duration of the test stimulus, the absence of any significant difference between the "adapt equal" and the "adapt longer" conditions in the present study suggests that there was no duration aftereffect after repetitive exposure to a relatively long stimulus.…”
Section: Discussionsupporting
confidence: 90%
“…Also, its negative duration aftereffect has been shown to be tuned around the adaptation duration (Heron et al, 2012), contingent on pitch and temporal order (Walker and Irion, 1979), but not on visual orientation (Li et al, 2015b) or visual hemifields (Li et al, 2015a). These results imply that duration adaptation involves modality-dependent and interval-independent clock systems.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…According to previous studies, the duration aftereffect arises in both vision and audition (Walker et al, 1981; Heron et al, 2012; Li et al, 2015b), with stimuli of both sub- and supra-second visual durations (Shima et al, 2016), is modality specific (Heron et al, 2012; Li et al, 2015b), tuned around the adapting duration (Heron et al, 2012), contingent on pitch and temporal order (Walker and Irion, 1979; Walker et al, 1981), but not on visual orientation (Li et al, 2015b) or visual hemifield (Li et al, 2015a). Because of its analogy with other sensory adaptation phenomena, a neural adaptation model has been proposed to explain this aftereffect of perceived duration (Walker et al, 1981; Heron et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…Whilst there are a number of conflicting findings within the visual adaptation literature, the overarching message is that the perception of duration of dynamic visual events appears driven by modality specific mechanisms (Li et al, 2015). Given the fact that adaptation to a stimulus reduces the amount of neural activity associated with that stimulus (Andrews, 1964; Clifford et al, 2007), one simple explanation for the effect of adaptation on perceived duration is that perceived duration of visual stimulus is directly driven by the neural activity elicited with that visual stimulus (Curran and Benton, 2012).…”
Section: Introductionmentioning
confidence: 99%